Early Pregnancy Maternal Serum PAPP-A and Urinary Protein-Creatinine Ratio as Predictive Markers of Pregnancy Induced Hypertension (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):267-74.The abstract of this article is available on the PubMed website